value of shock index in risk stratification of illness severity among patients in emergency department - Mawar Ayub, Mawar Ayub (2009)
Risk stratification of patient is very important, ~g at the time patient anive in Emergency Department. Wide range of patient's presentation sometimes can make them appear normal where their vital signs are nonnal but they actually deteriorate in time. We should not miss this group of patient as the mortality and morbidity rate will increase. Objectives of this study is to develop range of Shock Index value to risk stratify patient into 3 different groups which are low risk group, intennediate risk group and high risk group. This study was done in two centers which were Hospital Universiti Sains Malaysia (HUSM) and Hospital Kuala Lumpur (HKL) from June 2008 till November 2008. Patients older than 18 years old that came to Emergency Department of these two centers and meet the inclusion and exclusion criteria were enrolled. The first vital signs of patient were recorded by single reviewer and proceed with standard care of management. Then the disposition of patient was recorded by the same reviewer. Significant variables were initially identified. Then based on these values the range of Shock Index values were developed using the receiver operating characteristic (ROC) curve. A minimum value was identified, while the maximum value of 0.9 which has been extensively validated was applied. Total of 48 patients enrolled in this study. The significant parameters were systolic blood pressure (p=<O.OOI), diastolic blood pressme (p=0.006), heart rate (p=<O.OOI) and respiratory rate (p=0.004). Heart rate was the variable with most significant area under the curve (AUR) in ROC curve which 8re 0.844. From there, minimum value of Shock Index obtained was 0. 74 (sensitivity 80%, 1-specificity 74%). Thus, range of Shock Index values are <0. 74 as low risk group, 0. 75 - 0.9 as intennediate risk group and >0.9 as high risk group.